lncRNA GCAT1 is involved in premature ovarian insufficiency by regulating p27 translation in GCs via competitive binding to PTBP1 - Duan Li; Xiaoyan Wang; Yujie Dang; Xinyue Zhang; Shidou Zhao; Gang Lu; Wai-Yee Chan; Peter C.K. Leung; Yingying Qin (Elsevier, 2021)
Dysfunction of granulosa cells (GCs) leading to follicle atresia has been extensively studied as a major cause of premature ovarian insufficiency (POI), but the regulatory role of long non-coding RNAs (lncRNAs) in this process is still poorly understood. Here, we show that the lncRNA LINC02690 or GCAT1 (granulosa cell-associated transcript 1) is downregulated in GCs from patients with biochemical POI (bPOI), and we show a significant correlation between downregulated GCAT1 and serum levels of follicle-stimulating hormone and anti-Müllerian hormone. Downregulation of GCAT1 inhibited G1/S cell cycle progression and thus inhibited the proliferation of GCs. Mechanistically, we show that GCAT1 competes with cyclin-dependent kinase inhibitor 1B (CDKN1B) mRNA for polypyrimidine tract-binding protein 1 (PTBP1) binding, and thus decreased GCAT1 might promote PTBP1 binding to CDKN1B mRNA and thereby initiate CDKN1B protein (p27) translation. Together, our results suggest that downregulation of GCAT1 under conditions of bPOI inhibits the proliferation of GCs through PTBP1-dependent p27 regulation, thus suggesting a novel form of lncRNA-mediated epigenetic regulation of GC function that contributes to the pathogenesis of POI.